Utilização de análise por injeção em fluxo e em batelada com detecção amperométrica e eletrodos impressos para a determinação de ciprofloxacina - Stefano, Jéssica Santos (2016)
The present work presents the use of multi-walled carbon-nanotube modified screenprinted electrodes (MWCNT-SPEs) adapted for two different analytical systems (flow injection analysis - FIA and batch injection analysis - BIA) employing conventional amperometry for ciprofloxacin determination. Initially, cyclic voltammograms of the analyte were performed to define the best electrode and working pH. It was noted that screen-printed electrodes (SPEs) supplied current responses superior to those obtained by glassy-carbon electrode without modification. The SPE modified with multi-walled carbon nanotubes provided a slight increase in peak current when compared to unmodified carbon SPE. The electrolyte used in this study was 0.1 mol L-1 Britton-Robinson buffer in optimum pH of 4.0. Hydrodynamic voltammograms were obtained to select the working potential for amperometric studies. It was noted that ciprofloxacin has oxidation peak starting at +0.8 V, and with the rising of the potential, the current signal also increases, and the potential of +1.0 V was chosen to work in both systems BIA and FIA. For each one of the analytical methods, it was obtained optimal values of flow rate and injected volume, 42 and 153 μL s-1, and injected volume, 250 and 50 μL s-1, respectively for FIA and BIA. Under these conditions, repeatability study was performed and RSD values of 1.7 and 4.9 % for FIA and BIA, respectively. The methods presented linear range of 5 - 200 μmol L-1 for FIA (r = 0.998 and sensitivity of 0.0768 μA L μmol -1) and 5 - 150 μmol L-1 for BIA with stirring (r = 0.999 and sensitivity of 0.1115 μA L μmol -1). Therefore, it was possible to determine ciprofloxacin in two different pharmaceutical samples and the results obtained with the proposed methods were statistically similar to those obtained by capillary electrophoresis with 95 % confidence. The analytical frequency values were 99 and 130 injections per hour and detection limits were 0.06 and 0.07 μmol L-1 for FIA and BIA with stirring, respectively. Despite the higher sensitivity provided by higher flow rates of the BIA system, the detection limits using FIA and BIA were similar. However, the analytical frequency and precision of the BIA method was superior to the determination of ciprofloxacin, beyond the portable characteristics of this system.